Itinerant Barbaras: Anna Karenina’s Peripatetic Guardian Saints - Morris, Marcia A. (Christianity & literature, 2014)
In Anna Karenina, Tolstoy directs our attention toward several subsets of characters by conferring shared given names on them. This article focuses on one such subset—three minor characters named Barbara. Tolstoy derives his three Barbaras from the third-century St. Barbara, a protectress against violent death. All of the main protagonists of Anna Karenina are beset by fears of losing their place in the world, and several of them actively contemplate suicide. Three of them—Anna, Vronsky, and Kitty—are given a guardian-Barbara, who helps (or, in defiance of the protagonists’ expectations, fails to help) to ground them. Each of the Barbaras is an effective protectress in proportion to how well she hews to the structural paradigm provided by the Life of St. Barbara.